Comparison of Long-Term Fertility and Bleeding Outcomes after Robotic-Assisted, Laparoscopic, and Abdominal Myomectomy. (19th December 2016) - Flyckt, Rebecca; Soto, Enrique; Nutter, Benjamin; Falcone, Tommaso
Abstract : Background/Aims . To compare long-term fertility and bleeding outcomes of women who underwent robotic-assisted, laparoscopic, and abdominal myomectomy at our institution over a 15-year period. Methods . This was a retrospective cohort study of myomectomy patients 18–39 years old that had surgery between January 1995 and December 2009 at our institution. Long-term follow-up on fertility and bleeding outcomes was collected from the patient directly. The uterine fibroid symptom and quality of life survey was also administered to assess current bleeding patterns. Baseline characteristics were compared across groups. Univariable comparisons of fertility and bleeding outcomes based on surgical approach were made using analysis of variance, Kruskal-Wallis analysis of ranks, and Chi-square tests as appropriate. Results . 134/374 (36%) subjects agreed to participate in the study. 81 subjects underwent an open procedure versus 28 and 25 subjects in the laparoscopic and robotic groups, respectively. Median follow-up after surgery was 8 years. 50% of patients desired pregnancy following surgery and, of those, 60% achieved spontaneous pregnancy; the spontaneous pregnancy rate did not differ between groups. Additionally, UFS-QOL scores and/or subscores did not differ between groups. Conclusion . There is no significant difference in long-term bleeding or fertility outcomes in robotic-assisted, laparoscopic, or abdominal myomectomy.